2021
DOI: 10.3390/app11041455
|View full text |Cite
|
Sign up to set email alerts
|

Phytotoxic Activity and Growth Inhibitory Substances from Albizia richardiana (Voigt.) King & Prain

Abstract: Albizia richardiana, a fast-growing, large deciduous tree belonging to the Fabaceae family, grows well in hot and humid areas but mainly grows in the tropics of the Old World. The medicinal and other uses of Albizia richardiana are well documented, but the phytotoxic effects of this tree have not yet been investigated. We conducted this study to investigate the phytotoxic activity of Albizia richardiana leaves and to identify growth inhibitory substances for controlling weeds in a sustainable way. Aqueous meth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 65 publications
(53 reference statements)
2
9
0
Order By: Relevance
“…In addition, the results indicate that seedling length varied among the model plants, and the level of inhibition depended on the extract concentration (Figure 1). Similarly, several previous studies have also reported that the phytotoxic effect is concentration-dependent [48][49][50][51][52][53]. Moreover, many previous studies noted that test plant speciesʹ response varied depending on the types of phytotoxic substances [54].…”
Section: Biological Activity Of the Aqueous Methanol Extracts Of A Xylocarpa Leavesmentioning
confidence: 82%
“…In addition, the results indicate that seedling length varied among the model plants, and the level of inhibition depended on the extract concentration (Figure 1). Similarly, several previous studies have also reported that the phytotoxic effect is concentration-dependent [48][49][50][51][52][53]. Moreover, many previous studies noted that test plant speciesʹ response varied depending on the types of phytotoxic substances [54].…”
Section: Biological Activity Of the Aqueous Methanol Extracts Of A Xylocarpa Leavesmentioning
confidence: 82%
“…In our two previous studies, we examined the phytotoxicity of extracts of Albizia richardiana leaves against the seedling growth of Lepidium sativum , Medicago sativa L. (crop plants), Echinochloa crus-galli (L.) P. Beauv. and Phleum pratense L. (species of weeds) and observed notable growth suppression [ 38 , 43 ]. To validate those results, in this study, we also examined the allelopathic potential of the extracts of Albizia richardiana leaves against the growth of Lactuca sativa (lettuce) and Lolium multiflorum (Italian ryegrass).…”
Section: Discussionmentioning
confidence: 99%
“…Measuring the lengthening or shortening of shoots and roots is commonly employed to determine allelopathic activity [ 64 ]. In our two previous studies, two phytochemical substances, dehydrovomifoliol and loliolide [ 38 ], and another two allelopathic substances, 3-hydroxy-4-oxo-β-dehydroionol (novel compound) and 3-oxo-α-ionone [ 43 ], were isolated and identified from Albizia richardiana leaf extracts. In this study, we have also isolated another three phytochemical substances from Albizia richardiana leaf extracts: compounds 1 , 2 , and 3 ( Figure 3 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations